2006
DOI: 10.1182/blood-2005-09-3556
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of mouse Mayp/Pstpip2 causes a macrophage autoinflammatory disease

Abstract: IntroductionAutoinflammatory diseases are systemic conditions involving apparently unprovoked inflammation in the absence of autoantibody-and antigenic-specific T cells. A significant proportion of these diseases is caused by single gene mutations. Furthermore, the mutated gene remains to be discovered in a number of Mendelian inherited autoinflammatory diseases. 1 Identifying the genes involved is a first step toward elucidating the pathways involved in the inflammatory processes underlying these diseases. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
140
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 49 publications
2
140
0
1
Order By: Relevance
“…S1). Our findings demonstrating normal T-cell responses and activation in PSTPIP2-deficient mice are in agreement with an earlier report showing that osteomyelitic disease ensues in the absence of T cells in a separate Pstpip2 genetic mouse model (Pstpip2 lupo mice) (5). Collectively, these results suggest that osteolytic bone disease in Pstpip2 cmo mice may primarily be linked to dysregulated innate immune signaling.…”
Section: Significancesupporting
confidence: 93%
See 1 more Smart Citation
“…S1). Our findings demonstrating normal T-cell responses and activation in PSTPIP2-deficient mice are in agreement with an earlier report showing that osteomyelitic disease ensues in the absence of T cells in a separate Pstpip2 genetic mouse model (Pstpip2 lupo mice) (5). Collectively, these results suggest that osteolytic bone disease in Pstpip2 cmo mice may primarily be linked to dysregulated innate immune signaling.…”
Section: Significancesupporting
confidence: 93%
“…However, the roles of specific inflammatory pathways and immune cell networks in disease pathogenesis remain to be fully characterized for most bone disorders. Recently, missense mutations in the proline-serine-threonine phosphatase interacting protein 2 (PSTPIP2) were shown to cause a bone disease in mice that is characterized by osteomyelitis and bone deformity (4)(5)(6). In particular, the chronic multifocal osteomyelitis (cmo) mouse that carries a homozygous L98P missense mutation in PSTPIP2 (referred to as Pstpip2 cmo mice) develops a chronic autoinflammatory disease that resembles CRMO in humans (7).…”
mentioning
confidence: 99%
“…136 Moreover, mutations in a mouse-related protein PSTPIP2 causes a macrophage autoinflammatory syndrome, further delineating the importance of Pyrin and inflammasome regulation in autoinflammatory disorders. 137 …”
Section: Regulators Of Inflammatory Caspase Activationmentioning
confidence: 99%
“…[6][7][8][9] Proline serine threonine phosphatase-interacting protein 2 (PST-PIP2), also known as macrophage F-actin-associated and tyrosine phosphorylated protein (MAYP), is a Fes CIP4 homology domain (FCH) and Bin/Amphiphysin/Rvs (BAR; F-BAR) protein, predominantly expressed in the myeloid lineage. 10 It is rapidly tyrosine phosphorylated after activation of CSF-1 receptor (CSF-1R), [10][11][12][13][14] and exhibits reduced phosphorylation in mast cells in which c-Kit is inhibited. 12 The mouse Pstpip2 missense mutations, chronic multifocal osteomyelitis (cmo), L98P (Pstpip2 cmo/cmo ), and Lupo I282N (Pstpip2 Lupo/Lupo ) lead to similar autoinflammatory diseases, both characterized by splenomegaly, skin necrosis, and aseptic osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%
“…11,[14][15][16][17] The mutations result in complete (cmo) or partial (Lupo) PSTPIP2 protein deficiency, indicating that PSTPIP2 has anti-inflammatory activity. 11,14 Histologic studies of the cmo mice showed osteoclast-mediated bone resorption at sites of inflammation in caudal vertebrae, 15,17 and cultured cmo bone marrow cells exhibited increased vitamin D 3 -induced osteoclastogenic responses. 17 However, the molecular bases of these phenotypes were not elucidated.…”
Section: Introductionmentioning
confidence: 99%